Espécies superabundantes da fauna nativa e os desafios para seu controle - Silva, Aracelis Piovezani (Universidade Federal de São Carlos, 2023)
Anthropogenic disturbances have contributed to the overabundance of native species. This study aims to provide an overview of this issue. The discussion of new perspectives is quite helpful for decision makers when facing biodiversity conservation issues related to the identification and control of overabundant species. In addition to this review of studies carried out on superabundant species and possible control measures, we contextualize some impacts caused by superabundant species in the State of São Paulo, with data obtained from the Department of Wild Fauna Management - State Secretariat of Environment, Infrastructure and Logistics. We also analyzed the current legislation for the protection of native fauna, which allows for population control measures. As a result of the 158 articles analyzed, the term "superabundante" (overabundant) was the most frequently used (71.23%). Most of the studies were carried out in the USA, followed by Australia, where 82.19% described problems caused by mastofauna. The species with the highest number of citations (18) was Odocoileus virginianus. Although we analyzed publications dealing with health, economic or human-fauna conflict problems, the majority of publications dealt with environmental problems. Slaughter was the most frequently mentioned control measure. From these results, we can conclude that there are gaps in the research on superabundant species, especially on their control, in order to achieve the expected results of reducing their impact. Also, the adoption of a single concept to describe these species would be beneficial for communication on the subject. In the State of São Paulo, the species Hydrochoerus hydrochaeris, Linnaeus, 1766 (capybara) is found in superabundance in several regions, mainly in urbanized areas, and the current legislation allows actions to control superabundant fauna populations, which are mainly carried out by the private sector.
Overabundant species of native fauna and the challenges for their control
Keywords: Capivaras; Controle; Legislação ambiental; Impacto; Fauna nativa; Manejo reprodutivo; Abate; CIENCIAS BIOLOGICAS::ECOLOGIA::ECOLOGIA APLICADA